ADJEKTIVA INDERA DALAM BAHASA MINANGKABAU DI NAGARI SUNGAI TARAB - Hasanah, Nadya; Liusti, Siti Ainim (Universitas Negeri Padang, 2019)
The purpose of this study is to describe (1) the form of sensory adjectives in the Minangkabau language in Nagari Sungai Tarab, Sungai Tarab Subdistrict, Tanah Datar District, and (2) types of sensory adjectives in the Minangkabau language in Nagari Sungai Tarab, Sungai Tarab District, Tanah Datar. This type of research is a qualitative study using descriptive methods. The data source of this research is the Minangkabau language community in Nagari Sungai Tarab, Sungai Tarab Subdistrict, Tanah Datar. The findings of this study, namely (1) based on the shape, the amount of data on basic shape sense adjectives is more found than the derived form adjectives, (2) the most common form of derived adjectives is affixed sensory adjectives, and (3) based on the type, the amount of data the sense of sight adjectives are more numerous than the sense of smell adjectives, tactile sense adjectives, hearing sense adjectives, and taste sense adjectives.Keywords: Sensory Adjectives, Minangkabau language, Sungai Tarab